Professional competencies of mathematics teachers in the state of Kuwait in the light of modern international standards - Nashaat Abdelaziz, Abdelqader Baioumy (Penerbit Universiti Sultan Zainal Abidin, 2020)
The development of occupational competency, which matures and raises awareness within the educational process in general and specifically develops the instructor professionally. There has been much research regarding the matter by individual researchers and international scientific councils, their current research aims to investigate the reality of occupational competency and to its fulfilment towards mathematics instructors specifically in accordance to the obligatory international standards. This goal was achieved through the use of descriptive analytical methods of previous studies and known international standards. The results showed that interpersonal communication and class management were in the forefront, while cognitive skills and educational objectives were in the rear. This the result of a lack in preparatory programs given to the instructors during their service. Some studies also show that the teaching competency is relatively low. the results show that occupational competency related to subjective knowledge and the understanding of the student were relatively average. This is likely due to the personal inclinations of the instructor in the continuous application of traditional learning methods on one end, and the difference in culture between the instructor and learner one the other. As for the international standards for occupational competency set by (NCTM), (NSDC), and (NCATE) which were extracted and summarized in long term and short term planning and in terms of the competency of implementation and correction, it is recommended by current studies that more training courses be implemented to develop academic, occupational, and cultural competencies of mathematics instructors in light of recent international standards.